ASSESSMENT OF RURAL WOMEN’S KNOWLEDGE ON USAGE OF IMPROVED SHEA BUTTER PROCESSING TECHNOLOGIES IN ILORIN EAST LOCAL GOVERNMENT AREA, KWARA STATE, NIGERIA - Egbunonu, C. M.; Ogunjimi, S. I.; Alabi, O. O. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2019)
This paper assessed rural women knowledge level on usage of improved Shea butter processing technology in Ilorin East Local Government Area of Kwara State. Data were collected from 120 rural women in the area through structured interview schedule using multistage sampling technique. The findings revealed that majority (59.2%) were married and households depend on income realised from the sale of Shea-butter for livelihood. All the respondents used parboiling, a traditional method to soften Shea-butter fruits. The findings showed that 93.2% were knowledgeable on the use of grinding machine in processing Shea-butter. A greater percentage (62.5%) had low awareness on other improved technologies in processing Shea butter. Majority of respondents (90.0%) got information about improved Shea-butter processing from other processors. However, high cost of equipment was rated the major limiting constraint militating against the usage of improved Shea butter technologies in the area. The paper therefore highlights the need for government to create enabling environment through linking Shea butter processors with formal credit institutions and non-governmental organisations supporting rural women as a way of alleviating rural poverty.